Risiko Dislipidemia Pada Remaja Dengan Berat Badan Lahir Rendah - Toni M Aprami (The Indonesian Heart Association, 2007)
Background. Abnormal lipid profile is an independent risk factor for coronary artery disease. Some studies have shown that small for gestationa age (SGA) was associated with abnormal lipid profile in adolescence and adulthood. Since 16 years ago, district Tanjungsari (Sumedang-West Java) became a research area for cohort growth studyof Frontier for Health Foundation,incooperation with Research Unit of Medical Faculty University of Padjadjaran - Bandung. This study aims to assess whether SGA children are more prone to have abnormal plasma lipid profile.Methods and results.This study was performed to cohort population in Kecamatan Tanjungsari Kabupaten Sumedang-West Java, who was born between 1988-1990. The criteria of SGA based on WHO criteria (term infants, gestational age of > 37 weeks with birth weight of < 2500 grams). Inclusion criteria were SGA and AGA with postnatal growth up to 36 month adequately, complete birth weight and birth length records up to 36 months as well and birth weight and birth length during 12-14 years of age, willing to accompany in this study. After lipid profile examination was performed, validity and stratification data of 871 subjects, 229 subjects were complied with including criteria. With the simple random, 105 subjects of dyslipidemia were decided as the group of cases and the same number of control group were included as matching. There was no difference in general character-istic of both group (age, gender, birth weight, and birth length) p > 0.05. No significant difference between total cholesterol and LDL cholesterol level in subject with SGA compared with non-SGA, p > 0.05. Triglyceride level was higher found significant in subject with SGA compared with non-SGA, p=0.00004, however the HDL cholesterol level has a significant more less in subject with SGA compared with non-SGA, p=0.00004. Subject with SGA have an increase risk to develop of dyslipidemia compare with subject non SGA, odd ratio of 3.26, 95% CI 1.77-6.02; p=00003.Conclusions. Subject with prenatal growth retardation have an increase risk for dyslipidemia development.